Exploring the Relationship Between Swimming and Endurance Capacity: A Systematic Literature Review - Ridho Fatmawan; Komang Ayu Krisna Dewi; Gusti Agung Ayu Komang Sri Natasya Sastra Negara (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study investigates the association between swimming and endurance capacity through a systematic review of relevant literature. The review followed the PRISMA guidelines to ensure a transparent and structured selection process. Articles published between 2010 and 2025 were retrieved from databases such as Scopus, PubMed, Google Scholar, and ScienceDirect. After applying inclusion criteria, 15 studies were selected for analysis. The results demonstrate that swimming plays a significant role in enhancing both cardiorespiratory and muscular endurance among different groups, including trained athletes and general populations. Indicators such as VO₂ max, recovery heart rate, and endurance performance consistently improved following swimming interventions. From an exercise physiology perspective, these adaptations are linked to the combined influence of aerobic conditioning and water resistance. Nevertheless, the extent of improvement depends on training variables such as intensity, duration, and frequency. Some limitations were identified, including variations in methodology and a lack of long-term studies. Future research should focus on standardized approaches and broader participant groups. Overall, swimming can be considered an effective method for improving endurance capacity.